LncRNA TP53TG1 plays an anti-oncogenic role in cervical cancer by synthetically regulating transcriptome profile in HeLa cells - Cheng, Yi; Huang, Nan; Yin, Qingqing; Cheng, Chao; Chen, Dong; Gong, Chen; Xiong, Huihua; Zhao, Jing; Wang, Jianhua; Li, Xiaoyu; Zhang, Jing; Mao, Shuangshuang; et al. (Frontiers in Genetics, 2022)
Long non-coding RNAs (lncRNAs) have been extensively studied as important regulators of tumor development in various cancers. TP53TG1 is a newly identified lncRNA in recent years, and several studies have shown that TP53TG1 may play oncogenic or anti-oncogenic roles in different cancers. Nevertheless, the role of TP53TG1 in the development of cervical cancer is unclear. In our study, pan-cancer analysis showed that high expression of TP53TG1 was significantly associated with a better prognosis. We then constructed a TP53TG1 overexpression model in HeLa cell line to explore its functions and molecular targets. We found that TP53TG1 overexpression significantly inhibited cell proliferation and induced apoptosis, demonstrating that TP53TG1 may be a novel anti-oncogenic factor in cervical cancer. MechanisticallyFurthermore, overexpression of TP53TG1 could activate type I interferon signaling pathways and inhibit the expression of genes involved in DNA damage responses. Meanwhile, TP53TG1 could regulate the expression of a large number of RNA binding protein genes, thereby potentially affecting the alternative splicing of genes involved in cell proliferation or apoptosis regulation. Competing endogenous RNA (ceRNA) network analysis demonstrated that TP53TG1 could act as the sponge of several miRNAs to regulate the expression level of target genes. In conclusion, our study highlights the essential role of lncRNA TP53TG1 in the development of cervical cancer and discussessuggests the potential regulatory mechanisms.